Estimation of migratory history in female masu salmon Oncorhynchus masou (Brevoort, 1856) with the growth hormone pseudogene. (1st September 2016) - Yamamoto, T.; Suzuki, K.; Endo, T.; Kitanishi, S.
Summary: To estimate the migration timing, length, and location of females with the growth hormone pseudogene (GHp), trace element analyses were performed on the otoliths of 40 wild adult masu salmon, Oncorhynchus masou (12 males, 19 normal females, and nine females with GHp [all fish were 3‐ or 4‐years‐old]) caught during the reproductive season (September) from 2004 to 2010 in the Atsuta River in Japan. Sr concentrations at the end of the otolith translucent area formed during the winter suddenly increased in all individuals, suggesting that they had migrated in the spring. In addition, the estimated migration length and location of females with GHp indicated that they had spent a fixed period of 1 year in the ocean, suggesting that females with GHp have a similar migratory history as that of normal females.